RELATION BETWEEN PHYSICAL ACTIVITY LEVEL, LIVING PLACES AND COLLEGE STUDENTS (Fiep Bulletin - online, 2015)
The physical activity is now a priority in the Public Health.  One of the declared primordial factors of comment on the physical inactivity is the prevalence of sedentary and behaviors of risks to the health, in part, recurrent of the inexistence of one epidemiologist politics of monitoring the exposition of risk behaviors.  Where the estimates of insufficiently active the adult Brazilians would arrive approximately 60%.  In Brazil, it is made use of few data on the prevalence of sedentary in the different aged groups, with this, has a great difficulty to evaluate the behavior how much to the practical one of physical activities due to lack of standardized instruments and with good level of precision for use in population studies and different social and cultural contexts.  Objective:  The aim of this study was to analyze and to correlate the level of physical activity and the place of housing of living university students of two distinct areas of the state of Rio De Janeiro, the south zone and Baixada Fluminense.  Methodology:  It is a descriptive research of inquiry, which had to the data collecting without intervening with the study object.  It was used as volunteers of the research 88 individuals of both the sorts, university students who lived in any quarter of the south zone and in the Baixada Fluminense in the state of Rio de Janeiro. It was used as instrument for analysis of the level of physical activity the IPAC (International Questionnaire of Physical Activity) in the short version.  Used in diverse places, including Brazil, where it was validity in the versions short and long (CRAIG, 2003).  Moreover, also one was carried through registers in cadastre contends the place of housing of these volunteers .Os inquiries had been delivers to the individuals regularly registered in the forth period of the Course of Physical Education, inside of the proper university, where they would have to be filled and you deliver soon after that in the same place.  Techniques of descriptive statistics for analysis of the data had been used; being later used the non-parametric test Qui-square to analyze the level of significance in the interval of the 95% (p
Keywords: physical activity; place of housing; IPAC